CUSTOMER EXPERIENCE MANAGEMENT IN LARGE-SCALE EVENTS: UNDERSTANDING THE DETERMINANTS OF INTENTION AT JAKARTA FAIR - Shandra Widiyanti; Rudi Prasetyo Ardi; Anti Deisnasari (SEGMEN: Jurnal Manajemen dan Bisnis, 2026)
This study investigates how visitor experiences with physical facilities and promotional voucher systems influence their intention to revisit Jakarta Fair, Indonesia's largest annual trade and entertainment event. Through a quantitative survey of 300 visitors conducted between May and June 2024, we examine the relative importance of tangible facility experiences versus promotional incentives in shaping visitor loyalty. Our regression analysis reveals that both independent variables significantly predict revisit intention, accounting for 68.7% of variance. Notably, facility experience demonstrates stronger predictive power with a standardized coefficient of 0.452 compared to promotional vouchers at 0.387. These findings suggest a shift in visitor priorities from price-focused to experience-centered decision making. The research contributes to event management literature by proposing an integrated facility-promotion synergy model applicable to large-scale events in emerging markets